Bibliotherapy: A Framework for Understanding Pre-Service Primary Teachers’ Affective Responses to Learning and Teaching Mathematics - Sue Wilson; Steve Thornton (Southeast Asian Mathematics Education Journal, 2012)
This paper advocates bibliotherapy as a powerful tool through which teacher educators can analyze and interpret the affective responses of pre-service primary teachers. Pre-service teachers analyzed readings about school students’ learning, and reflected on and reconstructed their understanding of their own school experiences. This process facilitated a meta-affective change that enabled the pre-service teachers to reconsider their assessment of their capacity to learn and understand mathematics. We describe this change using the stages of bibliotherapy. This change enabled the pre-service teachers to approach their future teaching of mathematics with greater enthusiasm, and empowered them to construct positive projective identities.